The Inward light - Fielding, H. (Macmillan, 1908)
The secret of the east -- The golden hours -- The truth and the image -- The increasing purpose -- Evolution of the soul -- The wind -- Rooted in earth -- Rays of the infinite light -- A window on eternity -- One time, one truth -- Life that grows ever wider -- David -- Fate and freewill -- There is no night -- Doka, Aneitsa, Anatta -- The way -- That great gift of charity -- Man s faith and woman s -- The perfect fellowship -- Hell and heaven -- The understanding dream -- All truth is one